Cytokine polymorphisms in the study of Helicobacter pylori related gastric pathology - Murphy, Gwen (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2005)
Persistent local inflammation is now accepted as a risk factor in the development of a number of cancers. Non-cardia gastric cancer is thought to develop after a long lead-time whereby persistent inflammation, caused by Helicobacter pylori (H. pylori) colonisation of the gastric mucosa progresses to atrophic gastritis, intestinal metaplasia, dysplasia and carcinoma.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin